An experimental study of the stiffness and strength of cross-laminated timber wall-to-floor connections under compression perpendicular to the grain. (15th November 2022) - Schweigler, Michael; Akter, Shaheda T.; Sabaa, Stephen; Bader, Thomas K.
Abstract: In platform-type multi-story cross-laminated timber (CLT) buildings, gravity loads from upper floors, and vertical reaction forces from horizontal actions, like wind loads, cause substantial compressive forces in the CLT-floor elements. The combination of these high forces with a comparable low compression stiffness and strength perpendicular to the grain of timber, makes the compression perpendicular to the grain (CPG) verification of CLT an important design criterion. In this experimental study, CPG of CLT was investigated by means of typical wall-to-floor connections in CLT platform-type structures. CLT-wall elements were used for load application to transmit forces through the CLT-floor element by CPG. Compared to load application by steel elements, as it commonly is done in experiments, lower stiffness but similar strength were found for CLT walls. The study of different connection types showed the highest stiffness and strength for connections assembled with screws, followed by pure wood-to-wood contact, while connections with acoustic layers between the floor and wall elements showed the lowest stiffness and strength. In addition, these connections were tested for center and edge load position on the CLT-floor element. The strength for center and edge position compared to full surface loaded specimens increased linearly with the activated material volume, as determined by earlier proposed stress dispersion models. The stress dispersion effect was visualized by surface strain measurements using digital image correlation technique. Also, the stiffness increased with the activated material volume. Stress dispersion in the CLT-floor allowed to explain the increase in stiffness and strength with decreasing CLT-wall thickness. Strength values at different strain levels, and stiffness and strength increase factors suitable for the engineering design of CLT structures are provided. Highlights: Loading of CLT in compression perpendicular to the grain with steel and CLT. Loading by CLT gave lower connection stiffness but similar strength than loading by steel. Strength, but also stiffness, of CLT strongly depended on the position of the load. Screws and acoustic layers substantially influenced strength and stiffness. Surface strains from CLT tests agreed with assumptions of stress dispersion models.